Influence of biologic aging rate and arterial hypertension formon cerebral flow condition in aged and senile patients - Ye. D. Golovanov; N. N. Maslov; Ye. V. Nakoryakova; T. V. Osipova; S. N. Kozheko (Бюллетень сибирской медицины, 2007)
Results of cerebral hemodynamics condition assessment in dependence on central hemodynamics and biological aging rate are given in the article. Peculiarities of blood flow which influence on the development of chronic brain ischemia and mechanisms of its cellular compensation are revealed.